Synthesis of different layers of graphene on stainless steel using the CVD method - Ghaemi, Ferial; Abdullah, Luqman Chuah; Md Tahir, Paridah; Yunus, Robiah (SpringerOpen, 2016)
In this study, different types of graphene, including single-, few-, and multi-layer graphene, were grown on a stainless steel (SS) mesh coated with Cu catalyst by using the chemical vapor deposition (CVD) method. Even though the SS mesh consisted of different types of metals, such as Fe, Ni, and Cr, which can also be used as catalysts, the reason for coating Cu catalyst on the SS surface had been related to the nature of the Cu, which promotes the growth of graphene with high quality and quantity at low temperature and time. The reaction temperature and run time, as the most important parameters of the CVD method, were varied, and thus led to the synthesis of different layers of graphene. Moreover, the presence of single-, few-, and multi-layer graphene was confirmed by employing two techniques, namely transmission electron microscopy (TEM) and Raman spectroscopy. On top of that, electron dispersive X-ray (EDX) was further applied to establish the influence of the CVD parameters on the growth of graphene.